Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, Terhadap Belanja Pemerintah dan Pertumbuhan Ekonomi di Kalimantan Tengah - Haga, Ronni; Nugroho , Sanjayanto; Bancin , John Budiman; Christmas , Andreas F. (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
This study examines the influence of Local Own Revenue and Balance Funds on government expenditure and economic growth in Central Kalimantan. Economic development is a primary goal of local governments aimed at enhancing community welfare, requiring sufficient funding sourced from PAD and Balance Funds provided by the central government. Central Kalimantan, rich in natural resources, faces challenges in optimizing the utilization of these funding sources to support effective local government spending that promotes sustainable economic growth. The research employs a quantitative approach with panel data from 14 districts/municipalities over the 2010–2022 period. The findings indicate that both Local Own Revenue and Balance Funds and Balance Funds significantly affect government spending and, consequently, economic growth, highlighting the need for strategic financial management in regional governance to achieve better economic outcomes for the community